Applications of coherence scanning interferometry in additive manufacturing - Gomez Moreno, Carlos Alberto (2022)
Additive manufacturing (AM) is increasingly being used to fabricate fully functional parts. In this scenario, tolerances for dimensions and surface finish become crucial, especially for applications with stringent requirements. Therefore, the measurement of AM parts is essential to ensure adequate performance and to inform the manufacturing process. Typical metal AM surfaces are highly irregular, exhibiting a large number of high aspect-ratio topographic features, deep recesses and loose particles, while polymer AM surfaces are often translucent or have low reflectivity. Because of these characteristics, it can be challenging for any surface measuring technique to accurately measure the topography of metal and polymer AM surfaces. Coherence scanning interferometry (CSI) is one of the most accurate methods for areal surface topography measurement. CSI uses an interferometric objective lens and spatially extended, spectrally broadband illumination. When scanning a surface along the optical axis through the focus of the interferometric objective lens, interference fringes will be visible only within a narrow surface height range, corresponding to the zero group-velocity optical path difference of the interferometer. This phenomenon is known as ‘low-coherence interference’ and provides a highly accurate non-contact sensing mechanism to determine the three-dimensional topography of a surface. CSI has the ability to measure a wide range of surface types, from optically smooth to rough, as well as discontinuous surfaces without the 2π ambiguity that can arise with single-wavelength, phase-shifting interferometry. However, due to the limited numerical aperture of the imaging system, CSI may suffer from poor signal-to-noise ratios when measuring high-slope angle topographic features and surfaces with significant texture, or more generally, surfaces with low reflectance, compromising the ability to reliably determine surface heights. Although previous CSI technologies have shown difficulties when measuring AM surfaces, recent progress in the development of CSI allows a significantly enhanced detection sensitivity through the use of advanced analysis techniques, such as filtering of the light source spectrum bandwidth, high dynamic range lighting levels, oversampling (i.e. adjusting the number of camera acquisitions over each interference fringe) and sophisticated topography reconstruction algorithms. In this thesis, the effects of the aforementioned advanced analysis techniques on the measurement of typical as-built metal AM surfaces covering various textures and slope distributions are empirically investigated and systematically analysed. Guidelines are provided for the optimisation of the measurement of metal AM surfaces by balancing the total data acquisition time, the size of the measurement area, and the percentage of measured data points (i.e. data coverage). The detailed surface topography information captured with CSI is essential for providing feedback to the manufacturing process and for quality control of AM products. To validate this, a challenging case study has been considered. The feasibility of ink-jet printing a transparent polymer of tetrafluoroethylene, hexafluoropropylene and vinylidene fluoride (known as THV) to produce films of a few nanometres to several micrometres in thickness has been assessed using CSI. Solutions to minimise the ‘coffee ring’ effect and the formation of undesired wrinkle-like features on the surface when ink-jet printing THV are demonstrated. This work contributes to the field of polymer AM by providing insight into how to control and optimise the quality of ink-jet printed parts with the aid of surface metrology. Reducing measurement noise in CSI is an important consideration when measuring AM surfaces, in particular when the ability to capture data is compromised by poor signal-to-noise ratios. This thesis contributes to the understanding of the workings of measurement noise reduction methods and compares their effects when measuring surface topography in the presence of environmental vibration. The results provide guidance for the reduction of error in surface measurement for AM surfaces, and could be applied in a wider range of applications. The knowledge developed in this research is relevant to the manufacturing and scientific communities as CSI technologies are increasingly applied to the measurement of complex surfaces and in environments that resemble production areas more than metrology laboratories.